Microwave pyrolysis of lignocellulosic biomassa contribution to power Africa - Nomanbhay S.; Salman B.; Hussain R.; Ong M.Y. (Springer Verlag, 2023)
Biomass; Cracking (chemical); Diesel engines; Electric power generation; Energy policy; Energy resources; Engines; Fossil fuels; Fuels; Greenhouse gases; Microwaves; Oil shale; Palm oil; Planning; Pyrolysis; Bio oil; Electrical power generation; Electricity generation sectors; Microwave assisted technologies; Microwave-assisted pyrolysis; Nigeria; Oil palm biomass; Renewable energy generation; Renewable energy resources; biofuel; biomass; cellulose; electrical power; electricity generation; emission; fossil fuel; greenhouse gas; lignin; microwave radiation; pyrolysis; renewable resource; sustainable development; technology adoption; thermochemistry; Nigeria; Sub-Saharan Africa; Elaeis